Antimicrobial activity of conventional and plant-extract disinfectant solutions on microbial biofilms on a maxillofacial polymer surface - Guiotti, Aimée Maria [UNESP]; Cunha, Bruno Guandalini [UNESP]; Paulini, Marcela Borghi [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP]; Duque, Cristiane [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Brandini, Daniela Atili [UNESP]; Narciso de Oliveira, Derly Tescaro; Brizzotti, Natália Seron; Gottardo de Almeida, Margarete Teresa (Elsevier, 2016)
Statement of problem Dentists often note problems with infection in patients with maxillofacial prostheses. Conventional disinfection protocols are not always effective and may alter the properties of the polymer used in the prosthesis. Thus, the search for improved disinfection methods is important. Purpose The purpose of this in vitro study was to evaluate and compare the antimicrobial activity of conventional disinfectant solutions (water and neutral soap and 4% chlorhexidine) and plant extracts (Cymbopogon nardus and Hydrastis canadensis) on specimens of maxillofacial silicone contaminated with Candida albicans and Staphylococcus aureus biofilms. Material and methods Seventy-two silicone (MDX4-4210) specimens were fabricated (5×2 mm) and sterilized. Thirty-six were contaminated with C albicans (106 cells/mL) and 36 with S aureus (108 cells/mL) to evaluate the antimicrobial activity of the cleaning protocols. After incubation (37°C/72 hours), the specimens were divided into 5 groups: not disinfected (positive control), soaking in saline solution for 10 minutes, soaking in 4% chlorhexidine for 10 minutes, soaking in C nardus for 10 minutes, soaking in H canadensis for 10 minutes, and washing by hand with water and neutral soap for 30 seconds. The viability of cells was evaluated by XTT (2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide) assay and by scanning electron microscope analysis. The results were analyzed by ANOVA and the Tukey HSD test (α=.05). Results All disinfection solutions provided a statistically significant reduction in biofilm viability compared with the control group for both microorganisms (P<.05). Washing with water and neutral soap was significantly more effective in reducing biofilm viability than immersion in the disinfection solutions, with persistence of viable microorganisms between 1.05% for C albicans and 0.62% for S aureus after this cleaning protocol. Photomicrographs revealed that 4% chlorhexidine altered the surface of the polymer. Conclusions Within the limitations of this in vitro study, it was concluded that the cleaning protocols with different disinfectant solutions produced a significant reduction in the viability of C albicans and S aureus biofilms on the silicone polymer. Washing with water and neutral soap was the most effective protocol against both microorganisms.